Experimental study on the seismic behavior of high-performance cold-formed steel plate shear walls. (15th January 2022) - Shi, Yu; Luo, Zeqiao; Xu, Yunpeng; Zou, Yuxuan; Xu, Lei; Ma, Quantao
Highlights: Two kinds of full-scale CFS-SPSWs were tested under cyclic load. The SPSWs exhibited higher shear resistance and stable mechanical behavior. The screws between the central sheathing and edge members remain relatively intact. The SPSW with hat-section member as vertical edge member had good seismic behavior. Abstract: To study the seismic behavior of two types of walls under horizontal reversed-cyclic loading, 6 full-scale cold-formed steel plate shear wall (CFS-SPSW) specimens were designed. They each had three specimens. The effect of the vertical stiffener and the cross-section form of end stud on the seismic behavior of the cold-formed steel center-sheathed shear wall (CFS-C-SW), and the middle stud and peripheral self-tapping screw spacing on the seismic behavior of cold-formed steel skin-sheathed shear walls (CFS-S-SW) were considered. The failure modes, hysteresis and skeleton curves, characteristic values, energy dissipation capacity, stiffness and strength degradations were analyzed. The test results indicated that two types of walls exhibited high shear capacity and stable mechanical behavior. Furthermore, the shear capacity of CFS-C-SW could be improved significantly by setting vertical stiffeners or using hat-section end column. Moreover, the shear capacity and deformation capacity of CFS-S-SW could be improved significantly by reducing the peripheral screw spacing, but changing the middle stud spacing had no significant effect on its seismic performance.